2020
DOI: 10.1590/s0102-053620200312
|View full text |Cite
|
Sign up to set email alerts
|

Physiological potential of onion seeds stored in different packings and environments

Abstract: Storage is a fundamental step for maintaining seed quality after processing. Thus, in this study, we evaluated the physiological potential of onion seeds stored in different packings and environments. Impermeable, semi-permeable and permeable packings were tested under natural environment conditions (+19ºC), cold and dry chamber (10±2ºC and 33% RH) and cold chamber (16±2ºC and 60% RH), at 0, 90, 180, 270 and 360 days. The design was completely randomized in a 3x3x5 factorial scheme, with three replicates. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…According to Table 2, for the cold chamber environment at 45 days of storage, there was no difference between the packagings; on the other hand, at 90 and 135 days, seeds Changes in the water content of seeds in the present study can be explained by the fact that the cold chamber was frequently opened during some periods, causing fluctuations in temperature and humidity. And the permeable packagings do not offer any resistance to the exchange of water vapor between seeds and the environment in which they are stored; thus, the water content of seeds stored in permeable packagings varies according to variations in relative air humidity, because they are hygroscopic (Hornke et al, 2020). In the conventional environment, at 45 and 90 days of storage, the lowest percentage of the water content of seeds was found for the hermetic packaging (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…According to Table 2, for the cold chamber environment at 45 days of storage, there was no difference between the packagings; on the other hand, at 90 and 135 days, seeds Changes in the water content of seeds in the present study can be explained by the fact that the cold chamber was frequently opened during some periods, causing fluctuations in temperature and humidity. And the permeable packagings do not offer any resistance to the exchange of water vapor between seeds and the environment in which they are stored; thus, the water content of seeds stored in permeable packagings varies according to variations in relative air humidity, because they are hygroscopic (Hornke et al, 2020). In the conventional environment, at 45 and 90 days of storage, the lowest percentage of the water content of seeds was found for the hermetic packaging (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The concern about obtaining control of the environment (temperature and relative humidity) in cold rooms causes the seeds to reduce their metabolism, thus prolonging their physiological quality during the storage period. Hornke et al (2020) concluded that onion seeds maintained their physiological quality when stored in impermeable packaging for 360 days, regardless of the environment. The physiological seed quality was maintained in other packages when stored in cold or colddry rooms, with viability and vigor above 80% up to 180 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Polyethylene (Jaques et al, 2022) or hermetic packaging (Capilheira et al, 2019;Capilheira et al, 2020;Hornke et al, 2020) has been used in several studies to preserve the physiological seed quality. Considering these aspects, this study aimed to evaluate the physiological quality of corn seeds stored in different packaging and subjected to storage conditions in the central region of Brazil.…”
Section: Introductionmentioning
confidence: 99%